Problems in the historical sources for the reconstruction of the trajectory of Andrés Avelino Cáceres during the time of the Campaign of the Breña, from the civil war correspondent of the years between 1884 and 1885, and his rise to power in 1886 - Pereyra, Hugo (2018)
The majority of contemporary works about the trajectory of Andrés Avelino Cáceres, were dependent on the so-called Memoirs of this historical figure which were published after his death and are a work full of historical gaps and inaccuracies. The author of this article affirms that, in order to write a documented and objective study of Cáceres’ trajectory, one must utilize historical sources as the main documentary archive, prioritizing this over biographies, testimonies, reports or other research that is subsequent to the period of study in question. For this reason, he poses a general heuristic reflection about the historical sources used when trying to research the participation of Andrés Avelino Cáceres in the Campaign of the Breña, and during the phase of the civic conflict between 1884 and 1885.